BIOAKTIVITAS ASAP CAIR KULIT BUAH DURIAN SEBAGAI BAHAN PENGAWET PAPAN PARTIKEL Acacia mangium Wild - Rendra Antra Pardosi; Farah Diba; M. M. Dirhamsyah; H.A. Oramahi (Universitas Tanjungpura, 2012)
The study aims to determine the impact of using liquid smoke from durian rind concentrations and different pyrolysis temperatures on the durability of particle board. The experiment was conducted at the Laboratory of Wood Workshop, Laboratory Wood Processing, and Laboratory PT. Duta Pertiwi Nusantara. Experimental method using factorial completely randomized design (CRD) with 3 replications. Parameters measured were the durability of particle board (termite mortality and weight loss particle board). Result of the research showed that termite mortality ranged between 22% - 100% and the weight loss particle board ranged between 1,6901% - 7,7239%. Particle board are resistance to subterranean termites Coptotermes curvignathus Holmgren according Sornnuwat et al (1995) standard. Key words : Smoke liquid, particle boards, Acacia mangium, Coptotermes curvignathus Holmgren